Psychological flow and its relation to the personal characteristics of members of youth centers in Dohuk governorate - هوار معصوم عزيز محمد ا.د. عكلة سليمان الحوري (physical education and sport sciences college for women/ Baghdad University, 2021)
The subject of psychological flow and personality traits is one of the important topics in psychology, because it is one of the basic determinants of the behavior of the individual, and for this has received the attention of many scientists and researchers, hence the current research that seeks to build and apply the measure of psychological flow and personal characteristics of the members of the youth centers in Dohuk province and the research was based on the descriptive approach, as the research community included members of the youth centers in Dohuk province and their number (220) The research sample consisted of (60) affiliates, and summarized the objectives of the research as follows: To know the level of psychological flow and personal characteristics of the members of the youth centers of Dohuk governorate? To identify the relationship between the psychological flow and personal characteristics of the members of the youth centers of Dohuk governorate? In the light of the results of the research and its discussion within the limits of the sample, the researchers concluded the following: Members of youth centers in Dohuk province have a high level of psychological flow and personality traits in general.   There is a statistically positive correlation between both psychological flow and personality traits among members of youth centers in Dohuk governorate. The researchers recommend the following:   Conduct further studies related to psychological flow and personality traits and on mathematical and non-sports samples using the metrics studied in this study.   Building psychological programs aimed at enhancing the level of psychological flow and personality traits of youth center members in Dohuk governorate.